2015
DOI: 10.1088/1674-1056/24/11/117901
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of charge and discharge of PMMA samples due to electron irradiation

Abstract: Characteristics of charge and discharge of PMMA samples due to electron irradiation *Feng Guo-Bao(封国宝) a) , Wang Fang(王 芳) a) † , Hu Tian-Cun(胡天存) b) , and Cao Meng(曹 猛) a) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Apart from variation of direction, the energy of electron will transform during the inelastic scattering. [24,25] Here we can use the continuous slowing down approximation (CSDA) method to calculate the energy loss in each step. The energy loss dE/dS can be calculated by Bethe mode,…”
Section: Physical Calculation Modelmentioning
confidence: 99%
“…Apart from variation of direction, the energy of electron will transform during the inelastic scattering. [24,25] Here we can use the continuous slowing down approximation (CSDA) method to calculate the energy loss in each step. The energy loss dE/dS can be calculated by Bethe mode,…”
Section: Physical Calculation Modelmentioning
confidence: 99%
“…The electron yield of polymer thin films with ∼µm thickness is far less than 1 under high‐energy e‐beam irradiation. Therefore, excess electrons by inelastic scattering will be deposited inside the film forming the negative charge distribution 21–23 . However, the penetration range of e‐beam with beam energy >10 kV is larger than, or comparable with, the thickness of PMMA, and thereby some incident electrons may penetrate the film.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the accumulated electron in the bulk drifts toward the irradiation surface due to high conductivity and high electric field [9]. Feng et al thought that internal free electrons will run off to the ground in the form of leakage current due to charge diffusion and drift during the discharge process after irradiation, while trapped electrons remain undisturbed [10]. The accumulation of trapped charges establishes an internal electric field, affecting the injected electrons trajectories and charging energy loss.…”
Section: Introductionmentioning
confidence: 99%